A randomized controlled trial of a mobile application‐assisted nurse‐led model used to improve treatment outcomes in children with asthma. (12th August 2019) - Lv, Shaoxia; Ye, Xiaohong; Wang, Zhijiang; Xia, Wenfen; Qi, Yajuan; Wang, Weihan; Chen, Yuehua; Cai, Xiaohong; Qian, Xubo
Abstract: Aim: To evaluate the effectiveness of a mobile application‐assisted nurse‐led management model in childhood asthma. Background: Studies have shown that a nurse‐led asthma management model can improve asthma outcomes. However, the role of a mobile application‐assisted nurse‐led model in paediatric asthma management has not been studied well. Design: A multi‐centre randomized clinical trial. Methods: The trial was conducted between March 2017–March 2018. A total of 152 children (6 to 11.9 years old) were enrolled, with 77 children in the experimental group and 75 in the control group. All children received nurse‐led asthma management and other routine treatment measures, including inhaled corticosteroids. Meanwhile, a mobile application was used to manage asthma only for children in the experimental group. Primary outcome was frequency of asthma exacerbations. All outcomes were evaluated twice a month for 12 months. Results: Compared with the pre‐enrollment period, frequency of asthma exacerbations decreased in the post‐enrollment period in the two groups, with a greater decrease in the experimental group. Compared with children in the control group, children in the experimental group had better secondary outcomes, such as improved adherence, higher Childhood Asthma Control Test scores, decreased respiratory tract infections, days of antibiotic use, days of school absence, parental work loss, and medical expenses. Conclusion: A mobile application‐assisted nurse‐led management model decreased asthma exacerbations and improved secondary outcomes in children with asthma. Further research is needed to verify its validity in larger population samples. Impact: Children with asthma benefited from a nurse‐led asthma management model when combined with mobile application. This trial suggested that computer and Internet technologies should be incorporated into nurse‐led asthma strategy in paediatric asthma management. Trial registration: The current trial was registered online with the Chinese Clinical Trial Registry (registration number: ChiCTR1800016726). Abstract : 目的: 评估协助护理为主的手机应用管理模式在治疗儿童哮喘中的有效性。 背景: 研究证明, 以护理为主的哮喘管理模式能够改善哮喘治疗结果。然而, 协助护理为主模式的手机应用在儿科哮喘管理中的作用尚未得到很好的研究。 设计: 多中心随机临床试验。 方法: 该试验于2017年三月至2018年三月期间进行。共152名儿童(6 11.9岁)登记, 其中实验组77名, 对照组75名。所有儿童均接受由护士主导的哮喘管理以及其他一些常规治疗措施, 包括吸入皮质类固醇。同时, 手机应用仅用于实验组儿童哮喘的管理。主要结果是哮喘发作的频率。12个月内每月评估两次所有结果。 结果: 与登记之前相比, 两组的哮喘发作频率在登记以后均有所下降, 而实验组的下降幅度更大。与对照组的孩子相比, 实验组的孩子次要结果更好, 比如依从性得到了改善、儿童哮喘控制测试分数更高、呼吸道感染减少、使用抗生素天数、缺课天数、父母工作损失和医疗费用等。 结论: 协助护理为主的手机应用管理模式减少了哮喘恶化并改善了儿童哮喘的次要结果。需要进一步研究验证它在更大的群体样本中的有效性。 影响: 配合手机应用时, 儿童哮喘受益于护理主导的哮喘管理模式。本次试验表明, 应将计算机及互联网技术纳入儿科哮喘管理中以护理为主导的哮喘治疗策略。 试验注册: 目前的试验是在中国临床试验注册网上注册的(注册编号:中国临床试验注册中心编号1800016726)。